Pengaruh Kualitas Makanan Food and Beverage Departement terhadap Kepuasan Pelanggan di Oena Restoran Grand Orchardz Hotel, Jakarta - Gayatri, Dewa Ayu Prajna; Krisnawati, Inti (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2024)
In the hospitality industry, customer satisfaction is very important because it is the goal of hotel companies. Therefore, the food and beverage services provided by the food and beverage department must meet customer expectations, because customer satisfaction is the customer's emotional response in evaluating the customer experience using the services of the food and beverage department. The objects studied in this study were guests who used the services of the food and beverage department at Oena Restaurant Grand Orchardz Hotel Jakarta. This research uses quantitative methods with data collection techniques of questionnaires, observation and literature study. The sample for this study was 100 guests who used the food and beverage department at Oena Restaurant Grand Orchardz Hotel, and used the accidental sampling method. Data analysis techniques in this study used validity tests, classical assumption tests, coefficient of determination, t tests and simple linear regression analysis. Then the data is processed using IBM SPSS 26 software. The results of the calculation of the coefficient of determination (R2) have an influence on customer satisfaction, which is equal to 80%. Based on the results of simple linear regression analysis calculations with the t-test, a tcount value of 2.929 > 1.987 (ttable) was obtained with a p- value of 0.004. If the p-value is <alpha (5%), it can be interpreted that H1 is accepted while H0 is rejected or it can be interpreted that food quality (X) has an influence and is significant on customer satisfaction (Y) at Oena Restaurant grand Orchardz Hotel Jakarta